Morphological features of vasa vasorum in pathologically changed human great saphenous vein and its tributaries - Kachlík, D; Stingl, J; Sosna, B; Straka, Z; Lametschwandtner, A; Minnich, B; Fára, P (VASA. Zeitschrift fur Gefasskrankheiten, 2008)
BACKGROUND: The question whether the primary increase of vasa vasorum (VV) of venous wall (i) plays an initial role in varicogenesis or (ii) is an expression of impairment of the nutritional conditions in superficial veins of lower extremities is not unambiguously solved yet. The aim of the study was to describe the arrangement of the VV within the wall of the human great saphenous vein (GSV) qualitatively, and of its tributaries at different stages of varicosis and in other pathological states like thrombophlebitis or phlebosclerosis. MATERIAL AND METHODS: 22 patients deserving an aorto-coronary bypass surgery or GSV surgery were subdivided into three groups according to the staging of their varices and other pathology. The harvested GSV were prepared for light and scanning electron microscopy. One cadaverous specimen of GSV was injected with India ink. RESULTS: In specimens from reticular and primary large varices local intimal hyperplasia was regularly found, partially accompanied with a mild increase of VV. Tortuosities and irregular dilations of adventitial veins were also found. In patients with recurrent primary varices or thrombophlebitis severe intimal and medial hyperplasia, thrombosis and a striking increase of VV were found. The intima remained avascular in all cases. CONCLUSIONS: Remarkable increase of VV accompanies the most severe forms of varices as well as all cases of the extreme grades of phlebosclerosis, medial hyperplasia and thrombosis. We hypothesize that this increase in VV is rather a secondary vascular reaction to the impaired metabolic conditions within the venous wall than a primary varicogenic factor.
Keywords: Vasa Vasorum; Vascular Neoplasms; Models, Anatomic; Humans; lidé středního věku; Middle Aged; tromboflebitida; vena saphena; mužské pohlaví; anatomické modely; vasa vasorum; Saphenous Vein; ženské pohlaví; Varicose Veins; lidé; Thrombophlebitis; Aged; senioři; Male; vaskulární nádory; varixy; Female